Film “Big Brother 2018” Sebagai Inovasi Relasi Guru dan Siswa Perspektif Pendidikan Pembebasan Paulo Freire - Achmad Yulianto Widodo; Alaika M. Bagus Kurnia PS; Anugerah Ilma Dinilillahi; Moch Wahyu Qodarullah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This reaserch focuses on building the relationship between teachers and students in the film “Big Brother 2018” which shows the existence of liberation education. Using a descriptive-qualitative research method that provides details regarding how to build relationships between teachers and students in a medium as an inspiration to be applied in schools. A qualitative approach by supporting data on content analysis is expected to produce writings that media such as films can be good examples of teacher-student relationships. The relationship between teacher and student in the film shows freedom in teaching at school. The theory used in this research is the concept of Pauolo Freire in the liberation of education which offers an educational model of conscientization, facing problems and humanization. So that it can be obtained 1) conscientization education that teaches critical of reality 2) dealing with problems that make school students not only memorize the contents of books so that they pass with good grades on exams, 3) humanization which illustrates that teachers also learn from their students or non-formal subjects. subjects.